Short-lived minus-strand polymerase for Semliki Forest virus. - Sawicki, D L (1980)
Semliki Forest virus (SFV)-infected BHK-21, Vero, and HeLa cells incorporated [3H]uridine into 42S and 26S plus-strand RNA and into viral minus-strand RNA (complementary to the 42S virion RNA) early in the infectious cycle. Between 3 and 4 h postinfection, the synthesis of minus-strand RNA ceased in these cultures, although the synthesis of plus-strand RNA continued at a maximal rate. At the time of cessation of minus-strand RNA synthesis, two changes in the pattern of viral protein synthesis were detected: a decrease in the translation of nonstructural proteins and an increase in the translation of the viral structural proteins. Addition of cycloheximide and puromycin to cultures of SFV-infected BHK cells actively synthesizing both viral plus- and minus-strand RNA resulted within 15 to 30 min in the selective shutoff of minus-strand RNA synthesis. Removal of the cycloheximide-containing medium led to the resumption of minus-strand synthesis and to an increased rate of viral RNA synthesis. We conclude that the minus-strand polymerase regulates the rate of SFV plus-strand RNA synthesis by determining the number of minus-strand templates and that the synthesis of the minus-strand templates is regulated at the level of translation by a mechanism which utilizes one or more short-lived polymerase proteins.